The Effect Of Labor Adjustment Costs And Company Sıze On Tax Avoıdance Wıth Inflatıon As A Moderatıon Varıable - Khusniyah Tri Ambarukmi; Eko Ganis Sukoharsono; Syaiful Iqbal (Cita Konsultindo Research Center, 2023)
This study aims to test and prove empirically the effect of labor adjustment costs and company size on tax avoidance moderated by inflation in labor-intensive sector companies listed on the Indonesia Stock Exchange during 2018-2022. The sample collection technique used purposive sampling and obtained a sample of 200 observations. The analysis technique for testing the hypothesis uses multiple linear regression analysis, while the inflation measurement method uses Moderated Regression Analysis (MRA). The results showed that inflation that occurs as an external factor of the company can be a motivation that strengthens the influence of company size in tax evasion. Another result, namely the cost of adjusting the workforce as a cost attached to the taxpayer, is not a factor that makes companies do tax evasion even though the increasing occurrence of inflation as an external factor of the company.